DEVELOPMENT OF FOREST SPECIES IN THE ATLANTIC FOREST USING CONTROLLED-RELEASE FERTILIZER IN A PERMANENT PRESERVATION AREA - Holler, Karine Rosilene; Rossa, Uberson Boaretto; Farias, Daniel da Rosa; Sobreira, Fabrício Moreira (Floresta, 2025)
This study evaluated the initial development of native forest species of the Atlantic Forest under Controlled Release Fertilizer (CRF) doses in planting fertilization, aiming at forest recovery of an area of ​​riparian forest historically used in agriculture. The experiment was carried out in São Bento do Sul - SC. The design was in randomized blocks in a subdivided plot with three replications. In the plot, CRF doses of 0, 40, 80 and 120 g per hole were allocated and, in the subplot, native species (Handroanthus albus; Alchornea glandulosa; Inga marginata; Ocotea puberula; Campomanesia xanthocarpa; Allophylus edulis). 24 months after implantation, plant survival, height, collar diameter and crown diameter were evaluated. The survival percentage of the species was similar between the doses and differed among the species. The survival rate of O. puberula was 66.67% and above 87% for the others. In general, the doses of controlled-release fertilizer applied in the hole had a similar effect on the survival and development of the species. The lack of significant responses to fertilization can be attributed to pre-existing soil fertility conditions, whose history of use for agriculture promoted or maintained soil fertility at medium levels that tend to be satisfactory for native species of the Atlantic Forest. Using controlled-release fertilization technology in a permanent preservation area recovery project in the Atlantic Forest biome did not result in better initial development of the native forest tree species studied.